Shopping for others: how does inconsistency in online reviews affect purchase intentions differently? - Wang, Jiaying; Liu, Yang; Qiu, Zeguo; Zhao, Zhijie; Wang, Meng; Lan, Hong (Frontiers in Psychology, 2025)
IntroductionThe product reviews on e-commerce platforms often exhibit inconsistencies in consumer opinions. This raises the question: when consumers purchase products for others, do they place greater importance on inconsistent online reviews? To address this issue, this study explores the impact of online review consistency, social distance, and product type on consumer purchase intentions, based on the theories of psychological distance and construal level. It focuses on examining the moderating roles of social distance and product type in this process.MethodsA scenario-based experimental design was employed to test the hypotheses, with analysis of variance and simple effects tests used for data analysis. Study 1 utilized a 2 (inconsistency of online reviews: inconsistent/consistent) × 2 (social distance: close/remote) between-subjects design. Study 2 employed a 2 (inconsistency of online reviews: inconsistent/consistent) × 2 (social distance: close/remote) × 2 (product type: experience/search) design. Participants in each group were exposed to different experimental conditions and evaluations to assess the impact of online review consistency, social distance, and product type on consumer purchase intentions.ResultsThe study finds that inconsistency in online reviews significantly negatively impacts consumers’ purchase intentions, with ambivalent attitudes serving as a mediating factor. Under the influence of social distance matching effects, consumers exhibit lower purchase intentions when purchasing for a distant social relationship (i.e., with a remote social distance) compared to when purchasing for a close social relationship (i.e., with a close social distance), in situations involving inconsistent reviews. However, no significant difference is found in situations with consistent reviews. Product type further moderates the impact of social distance on the effect of online review inconsistency on consumers’ purchase intentions. Specifically, when consumers face inconsistent online reviews and the product recipient is a close relationship, their purchase intention for experience products (vs. search products) is lower. In contrast, when the recipient is a distant relationship, the difference in purchase intention is not significant.DiscussionThe findings of this study provide support for the mechanism through which online review inconsistency affects consumer purchase intentions, offering a new perspective for future research on the impact of review inconsistency. Additionally, it provides theoretical support for businesses and companies engaged in online marketing on e-commerce platforms.